2019
DOI: 10.1590/s0104-12902019180797
|View full text |Cite
|
Sign up to set email alerts
|

“O problema é a enorme produção de espermatozoides”: concepções de corpo no campo da contracepção masculina

Abstract: Resumo Desde o final dos anos 1960, há tentativas de produção de um contraceptivo masculino reversível com eficácia equivalente à da pílula anticoncepcional. Até hoje, esse produto não foi lançado, e as justificativas para tal baseiam-se em entraves de ordem política, econômica, cultural e biológica. O argumento do obstáculo fisiológico tem bastante proeminência nessas explicações e será o nosso foco neste artigo. Com base nos estudos de gênero e ciência, buscamos compreender como esse raciocínio aparece no tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Uma das justificativas para a inexistência da pílula masculina reside na concepção do corpo feminino como mais apto a intervenções farmacológicas do que o corpo masculino, representado como mais "complexo" (PEREIRA; AZIZE, 2019a). No escopo dos argumentos que sustentam a desigualdade de gênero respaldados na biologia, a concepção de que o ciclo menstrual e a produção de óvulos, por exemplo, seriam processos considerados mais simples quando comparados à espermatogênese, facilitaram o desenvolvimento de anticoncepcionais femininos (LEAL; BAKKER, 2017;AZIZE, 2019b).…”
Section: Introductionunclassified
“…Uma das justificativas para a inexistência da pílula masculina reside na concepção do corpo feminino como mais apto a intervenções farmacológicas do que o corpo masculino, representado como mais "complexo" (PEREIRA; AZIZE, 2019a). No escopo dos argumentos que sustentam a desigualdade de gênero respaldados na biologia, a concepção de que o ciclo menstrual e a produção de óvulos, por exemplo, seriam processos considerados mais simples quando comparados à espermatogênese, facilitaram o desenvolvimento de anticoncepcionais femininos (LEAL; BAKKER, 2017;AZIZE, 2019b).…”
Section: Introductionunclassified
“…Even so, until now there is still a very lack of male participation in following MOP contraception or vasectomy [5]. The cause of the low participation of men in the MOP method of family planning is that there are still many people who do not know about the existence of contraception for men other than condoms, making men ultimately unable to participate directly in the use of contraception, but also because of negative attitudes and thoughts about male contraception, thinking that family planning is a duty [6] [7]. women are not the responsibility of men even though the regulation of pregnancy and family welfare is a shared responsibility, not to mention the bad stigma that grows in society about vasectomy which makes people think that vasectomy is the same as castration, vasectomy interferes with ejaculation and erection as well as sexual relations, wife support also many wives are worried that if their husbands use vasectomy contraception, their husbands can have sexual relations with other people without fear of getting pregnant [3] [8].…”
mentioning
confidence: 99%
“…Therefore, this study recommends that more campaigns be carried out to enlighten the public in particular men benefit from vasectomy as a form of family planning and also men should be included in The issue of family planning has changed the current perspective that family planning is only for women [11] [10].The BKKBN also revealed that the problem of public knowledge is that there are still people who do not know at all that the existence of contraception for men affects the participation of men in family planning so that knowledge is one of the factors that influence the low selection of male contraceptives [12] [13]. By knowing what factors cause the low participation of male couples of childbearing age, it is hoped that it can be an evaluation for midwives in particular to be able to increase the participation of male couples of childbearing age to MOP contraception [14] [7].…”
mentioning
confidence: 99%